Effects of Tax Supervision and Socialization on Village Fund Tax Revenue Mediated by Taxpayer Compliance Level - Rusman Ruslan; Faizul Mubarok; Andi Harmoko Arifin (Jurnal Riset Perpajakan: Amnesty, 2026)
Village Funds have become a strategic instrument for accelerating rural development in Indonesia, while simultaneously increasing the complexity of village-level tax administration and the need to optimize tax revenue. However, previous studies have primarily focused on village treasurers, providing limited understanding of the strategic role of Account Representatives (ARs) in promoting taxpayer compliance and improving tax revenue performance. This study investigates the effects of tax supervision and tax socialization on Village Fund tax revenue, with taxpayer compliance serving as a mediating variable. Grounded in Compliance Theory and Stewardship Theory, the study develops an integrated mediation framework to explain the behavioral and administrative mechanisms underlying tax revenue optimization. A quantitative explanatory design was employed using survey data collected from 175 Account Representatives working in Primary Tax Service Offices across South Sulawesi, West Sulawesi, and Southeast Sulawesi. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that tax supervision significantly improves both taxpayer compliance and Village Fund tax revenue, whereas tax socialization significantly enhances taxpayer compliance but has no direct effect on tax revenue. Taxpayer compliance emerged as the strongest determinant of tax revenue and mediated the relationships between tax supervision, tax socialization, and tax revenue, acting as a partial mediator in the former relationship and a full mediator in the latter. These findings suggest that educational initiatives alone are insufficient to improve tax revenue unless they successfully foster compliant taxpayer behavior. The study contributes to tax administration literature by integrating governance and behavioral perspectives while highlighting the strategic role of ARs in strengthening sustainable taxpayer compliance and optimizing Village Fund tax revenue.